Upaya Guru PAI Dalam Menumbuhkan Sikap Toleransi Beragama Antar Siswa di Lingkungan SMA Negeri 2 Kendari - St. Fatimah K; Salam Inci; Husain Insawan (Yayasan Ishlahul Muslimin Konawe Selatan, 2025)
This study aims to describe the efforts of Islamic Religious Education (IRE) teachersin fostering religious tolerance among students atKendari State Senior High School 2. The background of this study stems fromthe importance of tolerance in social life, especially in schoolswith religious diversity, such as Islam, Christianity, Catholicism, and Hinduism.This study uses a descriptive qualitative approach with data collection techniquesin the form of interviews, observations, and documentation. The subjects ofthe study are PAI teachers, while the informants include the principal,vice principal, and students from various religious backgrounds. The results of the research show that PAI teachers at Kendari 2 State Senior High School madevarious efforts to instil tolerance, including emphasising theaffective aspect of learning, setting an example through their daily behaviour, internalising humanistic Islamic values, andcreating space for interfaith dialogue in the classroom. In addition, teachers alsocultivate tolerance through inclusive religious activities, such asImtaq activities for Muslim students and spiritual guidance fornon-Muslim students every Friday. Supporting factors in this success includethe school's commitment to diversity, the full support of the entire school community,and the existence of inclusive school policies. This study concludes that the efforts of Islamic Religious Education teachers contribute greatly to creating a harmonious and tolerant school environment.